Financial factors and labour market fluctuations - Yahong Zhang (Bank of Canada, 2011)
What are the effects of financial market imperfections on unemployment and vacancies? Since standard DSGE models do not typically model unemployment, they abstract from this issue. In this paper I augment a standard monetary DSGE model with explicit financial and labour market frictions and estimate the model using US data for the period 1964:Q1-2010:Q3. I find that the estimated degree of financial frictions is higher when financial data and shocks are included. The model matches the aggregate volatility in the data reasonably well. In particular, for the labour market, the model is able to generate highly volatile unemployment and vacancies, and a relatively rigid real wage. Further, I find that the financial accelerator mechanism plays an important role in amplifying the effects of financial shocks on unemployment and vacancies. Overall, financial shocks explain about 37 per cent of the fluctuations in unemployment and vacancies.
Keywords: E32; E44; J6; 330; Economic models; Financial markets; Labour markets